PENGARUH PERSEPSI RESIKO, PERSEPSI KEBERMANFAATAN DAN GAYA HIDUP YANG DIANUT TERHADAP PERILAKU PENGGUNAAN KARTU KREDIT - Yennida Parmariza; Septiani Juniarti (Jurnal Ilmiah Manajemen dan Bisnis, 2017)
This research aims to know influence of perceived risk, perceived benefit and life style onbehavior of using credir card by card holders. This object for this research is in MercuBuana University, especially for lecturers on Faculty of Economic and Business.Thesampling technique used purposive sampling and type of causal research method.Hypothesis testing using Partial Least Square (PLS) with the both of method Cronbach’sAlpha and Composite Realiability. The result of this research show that perceived riskvariable gives significant influence towards the behavior of using the credit card,Therefore, the early assumption is accepted. In the other way, perceived benefit dan lifestyle has not influence toward the behavior of using credit card. So,There are twoindependent variable does not support the hyphotesis and one independent variablesupport the hypothesis.